Humanism In Pancasila Democracy - Winanda, Aprilia Catur Anggun; Moza Zaki Fadillah Lubis; Reza Ramadhany; Salsabila (Lembaga Studi Agama dan Masyarakat Aceh, 2025)
This research is based on the importance of strengthening humanist values in the Pancasila Democracy system which has often not been manifested in the practice of national and state life. The purpose of this research is to identify the principles of humanism in Pancasila Democracy, analyze obstacles in its application, and can strengthen human values in the Indonesian democratic system. This research uses a descriptive qualitative approach with literature studies from literature studies, journals and books on philosophy, education, and national thought. The main findings include that Pancasila Democracy contains humanistic principles, such as respect for human dignity, social justice, deliberation, solidarity, and political ethics. However, the application of these values is still hampered by weak character education, discrimination, and lack of space for dialogue. The results of this study show that the value of humanism in Pancasila Democracy has a strong foundation, but it needs to be strengthened through a more contextual implementation strategy. His recommendations include strengthening Pancasila-based character education, bureaucratic reform, and building a space for social dialogue.